Physiological and transcriptomic analyses provide preliminary insights into the autotoxicity of Lilium brownii - Zhong, Shumin; Guo, Chuibao; Su, Lu; Jiang, Han; Wang, Xue-er; Shi, Li; Li, Xiaogang; Liao, Xiaolan; Xue, Jin (Frontiers in Plant Science, 2024)
Lilium brownii F. E. Brown ex Miellez var. viridulum Baker (Longya lily) is a variety of Lilium brownii F.E. Br. ex Miellez. We used HS-SPME and GC-MS to screened the tissues of L. brownii roots, stems, bulbs, and leaves and obtained 2,4-DTBP as an autotoxic substance for subsequent analysis. 2,4-DTBP was highly autotoxic in some treatment groups. Based on changes in physiological indicators, we carried out transcriptomic analysis to investigate the mechanisms of autotoxicity of substances on L. brownii and obtained 188,505 Unigenes. GO and KEGG enrichment analyses showed that L. brownii responded differently to different concentrations and treatment times of 2,4-DTBP. We observed significant changes in genes associated with ROS, phytohormones, and MAPK signaling cascades. 2,4-DTBP affects chloroplasts, the integrity of the respiratory electron transport chain, and ribosomes, causing L. brownii autotoxicity. Our findings provide a practical genomic resource for future research on L. brownii autotoxicity and evidence for the mechanism of action of autotoxic substances.